Succession of Throne by Women and Myths in Yogyakarta Sultanate - Sigit Surahman; Annisarizki Annisarizki; Rina Sovianti (International Journal of Multidisciplinary Approach Research and Science, 2025)
The phenomenon of female succession to the throne in the Yogyakarta Sultanate raises important issues regarding the legitimacy of power, patriarchal traditions, and socio-cultural change within the Javanese royal context. This research problem stems from the tension between traditional Mataram Islamic values, which place male leadership as the norm, and the emerging opportunities for women to occupy top positions within the palace structure. Previous studies have shown that discourses about women in Javanese culture are often associated with myths, sacred symbols, and ambivalent gender constructions, thus opening up space for debate regarding their position in traditional politics. This research uses qualitative interpretive methods combining observation, in-depth interviews, and literature review. The findings indicate that female succession to the throne is not simply an internal political phenomenon but is also closely related to myths that shape public perception, both as a symbol of power and a source of controversy. Furthermore, this process challenges the dominance of the patriarchal system and encourages a reinterpretation of Javanese cultural values. The study's conclusion confirms that women's involvement in succession to the throne reflects historical, political, and cultural dynamics and marks a significant shift in the socio-economic structure of the Yogyakarta Sultanate, both in the present and for its future development.